HUBUNGAN KUALITAS PELAYANAN KESEHATAN RAWAT JALAN DENGAN TINGKAT KEPUASAN PASIEN PESERTA JAMINAN KESEHATAN NASIONAL DI RSU MUHAMMADIYAH SUMATERA UTARA - Hasbina Wildani; Muhammad Badiran; Anto J Hadi (Jurnal Komunitas Kesehatan Masyarakat, 2020)
Hospital services provide services that are sold to customers. The superiority of a product depends on the uniqueness of the package offered whether it is as expected. Patient satisfaction becomes a benchmark because they are not satisfied to leave the hospital and become a competing customer. Outpatient visits at Muhammadiyah General Hospital in North Sumatra have increased but it does not immediately make them feel satisfied with the hospital. This study aims to determine the relationship of service quality with the satisfaction of JKN outpatients in North Sumatra Muhammadiyah Hospital. This type of research is cross sectional and this study was conducted from November 2019. Population is patients who are visiting Obgyn Poly, Child Poly, Internal Medicine and Surgical Poly as many as 299 visits per month with a sample of 75 respondents and sampling by accidental sampling. Data analysis methods used were chi square and logistic regression tests. The results showed that factors related to outpatient satisfaction were tanglibility (p = 0.016), reliability (p = 0.021), responsiveness (p = 0.001), assurance (p = 0.001), and empathy (p = 0.001). The conclusion is that there is a relationship between tangibility, reliability, responsiveness, assurance and empathy with outpatient satisfaction. It is expected for hospitals to retain customers and increase the number of visits, namely by improving the quality of service and completing infrastructure that is still lacking, so that patient satisfaction is fulfilled and patients become loyal.